The effect of a proposed sports program on improving the health status of type 2 diabetic patients - Hussein, Jasser (Journal of Physical Education, 2017)
The objective of this research is to show the effectiveness of exercise program proposal to improve the health status of patients with diabetes, and to achieve that, the researcher built a sports program based on the results of previous studies and researches in this area, The program included many of the units and sports that rely on walking to morning and evening for a period of Eight weeks, has been selected sample deliberately, made up of five patients with type II diabetes and those who have expressed a desire to volunteer and get involved in this program, was to measure pre and post to members of the sample according to the research variables are variables of the blood and include: (sugar, hemoglobin, Erythrocyte and leukocyte) and Alontheromitrip variables include: (weight, lipids). The results showed the existence of the impact of the program with a statistically significant variables Alontheromitrip while did not show statistically significant differences on the variables of blood with a note the low rate of sugar in the blood, although this decline is statistically significant difference between pre and post measurement